SEASONALLY VARIATIONS OF ARSENIC SPECIES IN CHICKEN MEATS CONSUMED BY TURKISH PEOPLE WITH HG-AAS - Kaya, Gokce; Karaaslan, Nagihan M.; Yaman, Mehmet (Parlar Scientific Publications (P S P), 2018)
The aim in this study is speciation and determination of arsenic in chicken meat matrix. For this purpose, chicken meat samples consumed commonly by Turkish people belonging to five different companies in Turkey were obtained from markets once per 15 days during 14 months. The samples were digested in microwave oven by using both nitric and hydrochloric acid. It was found that microwave digestion method can be used successfully in the speciation analysis of arsenic. The determination and speciation of As in solutions were carried out by hydride generation-atomic absorption spectrophotometry (HG-AAS). From the observed results, concentrations of As (V) were ranged between 3.0-14.0 ng g(-1) (mean 7.3 ng g(-1)) for breast tissues and 3.0-9.0 ng g(-1) (mean 5.1 ng g(-1)) for leg tissues. The concentrations of As (III) in all studied chicken tissues were found lower than the limit of detection (2 ng g(-1)).
Keywords: Arsenic speciation; chicken; HG-AAS; meat; microwave digestion